Knowing What You Need But Not What You Want: Affordances and Action-Defined Templates in Neglect - Glyn W. Humphreys; M. Jane Riddoch (Behavioural Neurology)
We examined search for target objects in a patient, MP, showing symptoms of left unilateral neglect. The conditions varied how the target was defined, the numbers of targets and distractors, and whether search was for multiple or single targets. We found that search was substantially improved when the target was defined by a description of its action rather than its name. This advantage for action-defined targets increased with larger display sizes. For both action and name-defined targets, there were also larger effects of the number of distractors when search was for multiple rather than single targets, even when the numbers of distractors were kept constant. However, these effects were increased for name-defined targets. The differences between action- and name-defined targets decreased when objects were replaced with words. The data suggest that search could be based on action-defined templates of targets, activated by affordances from objects. The action-defined templates facilitated detection and reduced MP's tendency to re-search displays.